The formula for the sacrament of communion in the Mochica language - Salas García, José Antonio (2007)
The purpose of this article is to translate from Mochica to Spanish the formula used to administer the sacrament of communion. As occurs with other Mochica texts that we have had occasion to interpret (Salas García 2008), the results of the translation show us texts that are not exactly the same in content as the versions of these sentences in Spanish.